1998
DOI: 10.1016/s0960-9822(98)70302-1
|View full text |Cite
|
Sign up to set email alerts
|

The Kit receptor promotes cell survival via activation of PI 3-kinase and subsequent Akt-mediated phosphorylation of Bad on Ser136

Abstract: The c-kit-encoded receptor protein tyrosine kinase for stem cell factor (Kit/SCF-R) is essential for the development of cells within the hematopoietic, melanogenic and gametogenic lineages [1]. SCF stimulation induces activation of phosphatidylinositol (PI) 3-kinase, which is required for SCF-induced mitogenesis and cell survival [2-4], and for activation of the serine/threonine protein kinase Akt [5-7]. Using Kit/SCF-R mutants, we found that, in response to SCF, Akt became activated and mediated phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
257
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(272 citation statements)
references
References 18 publications
12
257
3
Order By: Relevance
“…Comparisons between total cell lysates and phosphotyrosine purifications ( Figure 5) showed that KIT, PI3-K (regulatory and catalytic subunits), SHC and GRB2 were strongly tyrosine phosphorylated in a KIT-dependent manner in both GIST882 and GIST48 cell lines. These findings are consistent with KIT oncogenic activation of the RAS/RAF/MAPK and PI3-K/AKT pathways, which are regulated by activation of GRB2/SHC and PI3-K, respectively (Tauchi et al, 1994;Blume-Jensen et al, 1998). Recruitment of GRB2 and SHC adaptor proteins to RTK-derived oncogenes has been shown to be sufficient for morphological cell transformation and experimental metastases (Saucier et al, 2002), whereas Figure 6 (a-c) Cell density effects on KIT/PDGFR-dependent activation of kinase signaling proteins in GIST48, with and without KIT/PDGFR inhibition by PKC412.…”
Section: Discussionsupporting
confidence: 73%
“…Comparisons between total cell lysates and phosphotyrosine purifications ( Figure 5) showed that KIT, PI3-K (regulatory and catalytic subunits), SHC and GRB2 were strongly tyrosine phosphorylated in a KIT-dependent manner in both GIST882 and GIST48 cell lines. These findings are consistent with KIT oncogenic activation of the RAS/RAF/MAPK and PI3-K/AKT pathways, which are regulated by activation of GRB2/SHC and PI3-K, respectively (Tauchi et al, 1994;Blume-Jensen et al, 1998). Recruitment of GRB2 and SHC adaptor proteins to RTK-derived oncogenes has been shown to be sufficient for morphological cell transformation and experimental metastases (Saucier et al, 2002), whereas Figure 6 (a-c) Cell density effects on KIT/PDGFR-dependent activation of kinase signaling proteins in GIST48, with and without KIT/PDGFR inhibition by PKC412.…”
Section: Discussionsupporting
confidence: 73%
“…Several groups have since shown that Ser"$' can be specifically phosphorylated by PKB in itro and in transfected cells [115][116][117]. With the use of ion-exchange chromatography, PKB was found to be the major Ser"$' kinase in PDGF-treated fibroblasts, although other protein kinases, such as calmodulin-dependent protein kinase-II and p90RSK, can also phosphorylate Ser"$' in itro.…”
Section: How Does Pkb Protect Cells ?mentioning
confidence: 99%
“…PIP3 allows the recruitment of the phosphoinositide-dependant kinase 1 (PKD1), which activates the Akt/PKB protein. The proapoptotic Bcl2-family protein, Bad, and caspase 9 are inactivated by phosphorylation via Akt/ PKB [110]. The forkhead transcription factor (FKHR1), involved in the expression of proapoptotic factors Bim and FasL, is also inhibited by the action of Akt/PKB [111].…”
Section: Role Of the Pi3k Pathwaymentioning
confidence: 99%